Quantitative quality indicators for statistics – an application to euro area balance of payment statistics - Violetta Damia; Carmen Picón Aguilar (European Central Bank (ECB), 2006)
Quality is a subjective notion and encompasses all aspects of how well a product meets users' needs. It is inherently a multi-faceted concept that cannot be easily defined; any chosen definition is likely to change over time as new aspects gain importance following the evolving users' needs. The purpose of this paper is threefold; (1) to present a number of quantitative quality indicators, (2) to apply them to measure the quality of balance of payments (b.o.p.) data at the euro area level, and (3) to identify various aspects of data quality that may be enhanced, together with their interrelations with other quality dimensions. The indicators used are compatible with the IMF Data Quality Assessment Framework (DQAF), as defined for b.o.p. statistics, focusing mainly on revisions and consistency. The results obtained from such quantitative indicators may help compilers to set priorities in order to improve the quality of the euro area data still further in dimensions such as accuracy, reliability and serviceability. Additionally, this assessment may help users to understand better the quality of the data, to anticipate the possible size and direction of the forthcoming revisions, and to evaluate the impact of using different datasets in their analysis.
Keywords: 330; Zahlungsbilanzstatistik; Statistische Methode; Eurozone; EU-Staaten